The Influence of Case and Professional Variables on the Identification and Reporting of Child Maltreatment: A Study of Licensed Psychologists and Certified Masters Social Workers - Hansen, David J.; Bumby, Kurt M.; Lundquist, Lori M.; Chandler, Reginald M.; Le, Peter T.; Futa, Kristine T. (Journal of family violence, 1997)
Factors influencing the professional identification & reporting of child maltreatment were examined, drawing on mail survey data from 85 Certified Master Social Workers & 125 licensed psychologists in the Midwest. Analysis revealed that vignettes depicting lower socioeconomic status, persons of white race, & younger children recieved higher suspicion &/or reporting ratings than other vignettes, but the impact of those factors varied with the type of abuse depicted. Female professionals gave sexual abuse vignettes higher reporting ratings than males. Positive impact on the child, reports made in the prior year, & being a victim of marital/dating violence were professional factors positively associated with suspicion & reporting ratings, while negative impact on the parent was negatively associated with suspicion & reporting ratings. Differences between psychologists & social workers are discussed. 7 Tables, 27 References. Adapted from the source document.